Talpa europaea Linnaeus 1758 - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2018)
32. European Mole Talpa europaea French: Taupe d'Europe / German: Maulwurf / Spanish: Topo europeo Other common names: Common Mole, Mole Taxonomy. Talpa europaea Linnaeus, 1758, “Europe.” Restricted byJ. R. Ellerman and T. C. S Morrison-Scott in 1951 to “Engel- holm, Kristianstad, Sweden.” Talpa europaea is in subgenus Talpa and europaea species group. Talpa europaea from Italy is genetically and cranially highly divergent from the remaining populations and might represent a distinct species. Small blind moles occupying Thrace in Bulgaria and Turkey are usually classified as 1. levantis, but they are genetically closer to 1. europaea. Because no taxonomic name is available for this lineage, it is here retained in 7. europaea. Up to seven subspecies have been recognized in Europe, and this number was frequently reduced to two subspecies that differ in relative rostral breadth: nominate europaea and frisius named by P. L. S. Miller in 1776. Morphological diversity in 7. europaea is more complex, and four groups have been defined based on variability of cranial shape. In the past, many species of Talpa were regarded as synonyms of 1. europaea (altaica, caucasica, occidentalis, ognevi, romana, and stankovici). Subspecific taxonomy requires reassessment. Monotypic. Distribution. Most of Europe, from the British Is and NW France E to W Siberia as far E as Irtysh and Ob rivers, and from S Sweden, S Finland, and S Karelia (Russia) S to N Italy and N Balkans; marginally present also in NW Kazakhstan. In E Europe and in Asia the border roughly follows the extreme extension of the taiga in the N (northernmost record is from Pechora River close to 68°N) and the steppe-forest—steppe transition in the S. Present on some Is in the Baltic Sea and around Denmark (Oland, Funen, Zeeland, Bjgrng, Tasinge, Tung, Langeland, Riigen, Usedom, and Wollin), around Great Britain (Sky, Mull, Anglesey, Wight, and Jersey), offshore W coast of France (Ouessant and Ré), and on Cres (Croatia) as the only Mediterranean I. Descriptive notes. ...